Hijabi Metal Voice of Baceprot: Discourse on Identity, Gender and Religion in Digital Space / Hijabi Metal Voice of Baceprot: Wacana Identitas, Gender dan Agama di Ruang Digital - Pikri, Zainal; Muthmainnah, Inna (Alhadharah: Jurnal Ilmu Dakwah, 2024)
This study examines the intersection of religion, gender, and culture through the case of Voice of Baceprot (VOB), an Indonesian hijab-wearing metal band. Utilizing Kimberlé Crenshaw’s intersectionality theory and Laclau and Mouffe’s discourse analysis, the research analyzes YouTube viewer comments to explore how VOB’s identity as Muslim women metal musicians is constructed and contested. The study employs a qualitative approach, collecting comments from VOB’s most-viewed YouTube videos using Python-based scripts and analyzing them thematically and discursively. This methodology reveals competing narratives: critics perceive the hijab as incompatible with traditional metal aesthetics, while supporters celebrate its role in redefining gender and religious norms in popular music. By navigating these complex discourses, VOB challenges stereotypes within conservative Islamic norms and global metal culture, presenting the hijab as a symbol of personal choice and empowerment. The findings highlight how VOB redefines heavy metal as a global, inclusive genre and demonstrates the power of music to transcend cultural and religious barriers.